Modular, Flexible, and Continuous Plant for Radical Polymerization in Aqueous Solution. Issue 4 (28th April 2016) - Kohlmann, Daniel; Chevrel, Marie‐Claire; Hoppe, Sandrine; Meimaroglou, Dimitrios; Chapron, David; Bourson, Patrice; Schwede, Christian; Loth, Wolfgang; Stammer, Achim; Wilson, James; Ferlin, Patrick; Falk, Laurent; et al.
Abstract : A continuous and flexible pilot‐scale plant is designed for the production of acrylic acid homo‐ and copolymer in aqueous solution. On the basis of previous experimental lab‐scale studies the plant is built and equipped with Raman probes for monitoring the consumption of monomers. Demonstration experiments are carried out and results are satisfactorily depicted by theoretical calculations. Abstract : The European project F 3 Factory aims at designing small to medium scale plants consisting of standardized container assemblies for delocalized production of various chemicals. Within the framework of the F 3 Factory project, the design of a modular, multiproduct, and continuous plant for manufacturing water‐soluble polymers is addressed. Free radical polymerization in aqueous solution is examined through two industrial cases: polymerization of acrylic acid (AA) in the presence of chain transfer agent (CTA) and copolymerization of AA with one comonomer. A methodology for performing the transition from batch recipes to continuous operations is proposed. Offline and inline monitoring of monomer consumption is achieved using Raman spectroscopy combined with chemometrics. A modular pilot plant meeting the requirements of F 3 Factory project is designed and demonstrated at INVITE (Bayer, Leverkusen). The two polymerization processes are successively operated in the same pilot plant separated by an intermediate extensive washing. For each process, several polymer grades are produced by modification of reaction conditions (inlet flow of CTA or reactor temperature). Transition dynamics are characterized using inline monitoring. The flexibility of the modular plant is demonstrated.